Patriarchy and Women’s Emancipation in Indonesian Film: Marlina the Murderer in Four Acts and Perempuan Berkalung Sorban - Nabila Marasabessy (MUHARRIK: Jurnal Dakwah dan Sosial, 2021)
This study aims to analyze the differences in the concept of women's emancipation displayed by Marlina in the film Marlina the Killer in Four Acts and Anisa in the film Perempuan Berkalung Sorban. These films tell different stories about women who fight for their rights, but both have a storyline in which Marlina and Anisa are shackled to a patriarchal culture. This study uses data analysis based on John Fiske's television code theory and semiotic analysis with a gender approach. An in-depth analysis and study show the character of women's emancipation in the second film. First, the Marlina film, The Murderer in Four Acts, shows an emancipated female character who can live independently and dare to defend herself when insulted or sexually harassed by men. Women are also entitled to the same legal justice as men. Meanwhile, the concept of emancipation in the film Perempuan Berkalung Sorban shows the emancipated character of women who have the right to reject polygamy and gain extensive knowledge but remain in their nature as children, mothers, and wives. Women also have the right to express their thoughts and feelings and choose whom they will marry.